2002
DOI: 10.1074/jbc.m109862200
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor-induced p75-mediated Death of Cultured Hippocampal Neurons Is Age-dependent and Transduced through Ceramide Generated by Neutral Sphingomyelinase

Abstract: Binding of nerve growth factor (NGF) to the p75 neurotrophin receptor (p75) in cultured hippocampal neurons has been reported to cause seemingly contrasting effects, namely ceramide-dependent axonal outgrowth of freshly plated neurons, versus Jun kinase (Jnk)-dependent cell death in older neurons. We now show that the apoptotic effects of NGF in hippocampal neurons are observed only from the 2nd day of culture onward. This switch in the effect of NGF is correlated with an increase in p75 expression levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 69 publications
5
85
0
Order By: Relevance
“…As observed for other apoptotic stimuli, including trophic factor deprivation and Fas (Estévez et al 1998;Raoul et al, 2002), the mechanism of p75 NTR -induced apoptosis in motor neurons involves downstream production of nitric oxide and peroxynitrite formation (Pehar et al, 2004). In the present study, we found that the p75 NTR apoptotic pathway in motor neurons involved increased ceramide production and cytochrome c release into the cytosol, as observed in other cell types (Casaccia-Bonnefil et al, 1996;Kuner and Hertel, 1998;Brann et al, 2002;Bhakar et al, 2003). p75…”
Section: Reexpression Of P75supporting
confidence: 57%
“…As observed for other apoptotic stimuli, including trophic factor deprivation and Fas (Estévez et al 1998;Raoul et al, 2002), the mechanism of p75 NTR -induced apoptosis in motor neurons involves downstream production of nitric oxide and peroxynitrite formation (Pehar et al, 2004). In the present study, we found that the p75 NTR apoptotic pathway in motor neurons involved increased ceramide production and cytochrome c release into the cytosol, as observed in other cell types (Casaccia-Bonnefil et al, 1996;Kuner and Hertel, 1998;Brann et al, 2002;Bhakar et al, 2003). p75…”
Section: Reexpression Of P75supporting
confidence: 57%
“…To investigate this, we examined the involvement of ceramide, because the generation of ceramide following the activation of p75 regulates many aspects of neuronal response, including cell survival and apoptotic cell death by neurotrophins (24,28). Blochl and Sirrenberg (33) suggested the possibility that NGF affected dopamine release through the sphingomyelin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ceramide, which is produced by sphingomyelinase, is involved in NGF-mediated neuronal cell death (24,28). Therefore, we attempted to clarify whether ceramide production was involved in the NGF-induced glutamate release.…”
Section: Ngf Induced a Rapid Release Of Glutamate In Culturedmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of p75 NTR expression can induce apoptosis when there are low levels of Trk or when Trk is absent (10,11). Apoptosis occurs through increased ceramide production (12), activation of c-Jun N-terminal kinase (JNK1), and p53 (10,13). p75 NTR requires a co-receptor called sortilin to induce cell death (14).…”
mentioning
confidence: 99%